The Effect of Receivable Turnover, Working Capital Turnover, and Debt Ratio on Current Ratio in Mining Company - Rizal Achmad Maulana (Jurnal VOK@SINDO, 2015)
This study aims to determine the effect of receivable turnover, working capital turnover and debt ratio on current ratio in mining company. The population in this study are 39 companies listed on the Indonesia Stock Exchange during 2011 until 2014. The sampling technique used in this study is purposive sampling which covers 14 companies. This study uses multiple linear regression analysis. The results show that receivable turnover and working capital turnover does not affect the current ratio. Meanwhile, debt ratio has significantly influenced a company's current ratio. This proves that with high debt ratio, the creditors still trust the Indonesian mining companies to expand their business scale as well as increase production capacity and sales volume of mining products so as to provide additional revenue. Thus, the current ratio of the company will decrease.